(8x+1)(x-7)=(2x-3)(4x+5)

Simple and best practice solution for (8x+1)(x-7)=(2x-3)(4x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (8x+1)(x-7)=(2x-3)(4x+5) equation:


Simplifying
(8x + 1)(x + -7) = (2x + -3)(4x + 5)

Reorder the terms:
(1 + 8x)(x + -7) = (2x + -3)(4x + 5)

Reorder the terms:
(1 + 8x)(-7 + x) = (2x + -3)(4x + 5)

Multiply (1 + 8x) * (-7 + x)
(1(-7 + x) + 8x * (-7 + x)) = (2x + -3)(4x + 5)
((-7 * 1 + x * 1) + 8x * (-7 + x)) = (2x + -3)(4x + 5)
((-7 + 1x) + 8x * (-7 + x)) = (2x + -3)(4x + 5)
(-7 + 1x + (-7 * 8x + x * 8x)) = (2x + -3)(4x + 5)
(-7 + 1x + (-56x + 8x2)) = (2x + -3)(4x + 5)

Combine like terms: 1x + -56x = -55x
(-7 + -55x + 8x2) = (2x + -3)(4x + 5)

Reorder the terms:
-7 + -55x + 8x2 = (-3 + 2x)(4x + 5)

Reorder the terms:
-7 + -55x + 8x2 = (-3 + 2x)(5 + 4x)

Multiply (-3 + 2x) * (5 + 4x)
-7 + -55x + 8x2 = (-3(5 + 4x) + 2x * (5 + 4x))
-7 + -55x + 8x2 = ((5 * -3 + 4x * -3) + 2x * (5 + 4x))
-7 + -55x + 8x2 = ((-15 + -12x) + 2x * (5 + 4x))
-7 + -55x + 8x2 = (-15 + -12x + (5 * 2x + 4x * 2x))
-7 + -55x + 8x2 = (-15 + -12x + (10x + 8x2))

Combine like terms: -12x + 10x = -2x
-7 + -55x + 8x2 = (-15 + -2x + 8x2)

Add '-8x2' to each side of the equation.
-7 + -55x + 8x2 + -8x2 = -15 + -2x + 8x2 + -8x2

Combine like terms: 8x2 + -8x2 = 0
-7 + -55x + 0 = -15 + -2x + 8x2 + -8x2
-7 + -55x = -15 + -2x + 8x2 + -8x2

Combine like terms: 8x2 + -8x2 = 0
-7 + -55x = -15 + -2x + 0
-7 + -55x = -15 + -2x

Solving
-7 + -55x = -15 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-7 + -55x + 2x = -15 + -2x + 2x

Combine like terms: -55x + 2x = -53x
-7 + -53x = -15 + -2x + 2x

Combine like terms: -2x + 2x = 0
-7 + -53x = -15 + 0
-7 + -53x = -15

Add '7' to each side of the equation.
-7 + 7 + -53x = -15 + 7

Combine like terms: -7 + 7 = 0
0 + -53x = -15 + 7
-53x = -15 + 7

Combine like terms: -15 + 7 = -8
-53x = -8

Divide each side by '-53'.
x = 0.1509433962

Simplifying
x = 0.1509433962

See similar equations:

| 5(z+1)=4(z-8)+z | | 2q+58=-2+-4q | | y=-2cos(x) | | -2q+58=2+-4q | | (3/4×).(y/3) | | R/8=9 | | 1/2(4x=6)=0 | | -4x+.5y=1 | | 4a-4=8+2 | | x-32=-4x+23 | | x^3-9x^2+72x-260=0 | | 8m-6+8(m+2)=8m+42 | | 15g=20h | | a/4-3a/5=-7/2 | | -11=-99 | | Y=(2x-2)(3x+2) | | 2x-0.75=3.75 | | 5p-5=15 | | 10+3x-12=3x+2 | | x-32=4x+23 | | 13=t+2.1 | | 3x-6=-3x | | -m-17+14+12m= | | 22x=71.5(97.5-x) | | 3x-7+12-5x= | | 6x-35=14-x | | 9x-27=-6x+-12 | | -94-4x=122-12x | | 19x=-5x-6 | | 40=17x-y | | 49+x=10 | | 6x=3(6+24) |

Equations solver categories